Molecular characterization of Shiga toxin-producing Escherichia coli and enteropathogenic Escherichia coli of bovine origin - KAWOOSA, S S; HUSSAIN, I; WANI, S A; BHAT, M A (The Indian Journal of Animal Sciences, 2011)
One hundred ninety six and 49 Escherichia coli isolates from 170 diarrhoeic and 50 healthy calves, respectively, were screened for the presence of stXj, stx2' eae and ehxA genes. In calves with diarrhoea 43 (21.93%) isolates possessed at least one virulence gene targeted. Of these, 29 (14.790/0) possessed stx] and/or stx2 genes (Shiga toxin-producing Escherichia coli STEC), while 3 (1.53%) harboured eae alone (enteropathogenic Escherichia coli EPEC). FraIn healthy calves 14 (28.570/0) isolates possessed at least one of the virulence gene. Of these 11 (22.44%) were STEC \vhiIe 3 (6.12%) were EPEC. Statistically, there was no difference in prevalence of STEC and EPEe between healthy and diarrhoeic calves.Â